The role of public-private partnerships in selling, general, and administrative cost stickiness - Han Qing (Cogent Economics & Finance, 2023)
Public-Private Partnerships (PPP) which promotes public welfare is greatly supported by the China government. The authority endorsements relax financial constraints and promote operation efficiency. Using a sample of 9,733 firm-years in the empirical study, it is found that companies participating in PPP projects are associated with greater selling, general, and administrative (SG&A) cost stickiness, and it is more prominent in companies with severe financial constraints. Meanwhile, SG&A cost stickiness is stronger in companies carrying PPP projects in provinces with great amount of PPP investments which alleviates hardship of the government by issuing debts. To verify the causal link between PPP and cost stickiness, it is found that PPP projects can reduce relative changes between productions and demands in companies, implying PPP improve the bargaining power against suppliers and the control of manufacturing cost. Typical PPP projects have great public interest that should be reinforced by high-quality construction and commitments on investments, thus the marginal stickiness brings out incremental social benefit. The overall actual performance of PPP projects in China is good.
Keywords: 330; government debt; PPP; SG&A cost stickiness; supply Chain